AKIBAT HUKUM WANPRESTASI LESSEE DALAM PERJANJIAN SEWA GUNA USAHA (STUDI PUTUSAN NOMOR 690/PDT.G/2011/PN.JKT.SEL) - Ula, Robiul (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2023)
In order to support equitable development of the national economy, a large amount of capital is needed. The government as a regulator provides a solution by introducing leasing financing institutions. Leasing financing institutions are considered to be more capable of responding to aspects of public capital needs and more flexible in their implementation procedures than bank financial institutions that are generally known in the community. Leasing is a financing activity in the form of providing capital goods by the lessor to the lessee. leasing activities are not regulated in the Civil Code so that their implementation uses the principle of freedom of contract. The legal relationship that occurs between the parties in the lease agreement is a reciprocal relationship and when one of the achievements cannot be fulfilled by one of the parties, it can lead to a default dispute. In practice, it is often done by the lessee which causes losses to the lessor. So to protect the lessor, the lessee has a legal responsibility that he must fulfill in the event of a default. In this case, the author reanalyzes Verdict Number 690/Pdt.G/2011/PN.Jkt.Sel between PT. ITC Auto Multi Finance against Erick Rusmin. The purpose of this study is to find out and understand to what extent the liability of a tenant who does not fulfill the performance of a lease agreement that has been made and agreed upon previously is also to find out the suitability of the judge's legal considerations in deciding to request a lease default in Decision Number 690/Pdt.G/2011/PN.Jkt.Sel with the applicable legal provisions. By using normative legal research (doctrinal) which is elaborated with a statutory approach and a conceptual approach, as well as the use of primary, secondary, and non-legal materials for further deductive-inductive analysis, this research finds problems, including: what is the legal responsibility of the lessee who does not fulfill the performance in the lease agreement and whether the judge's consideration in the decision Number 690/Pdt.G/2011/PN.Jkt.Sel is in accordance with the applicable legal provisions. Keywords : Legal Responsibility, Default, Lease Agreement